The Effect of Facilities and Motivation on Learning Outcomes of High School Students in Gelumbang, Indonesia - Hariyanto, Dedy; Arafat, Yasir; Wardiah, Dessy (Yayasan Sembilan Pemuda Indonesia, 2021)
Qualified teachers play a very important role in improving learning process in schools. Teachers who are able to use facilities as learning resources will have a positive impact on student success at school. The more complete facilities in the school, the more motivated students will be in the learning process. The purpose of this study was to determine the effect of facilities and motivation on student learning outcomes at SMA PGRI Gelumbang. The type of research conducted was quantitative which analyze the questionnaire data, which is then analyzed using SPSS For Windows. The results of the study indicate that there is an influence of learning facilities and motivation together either simultaneously or partially on student learning outcomes in high school. This paper contibutes to more focus on facilities and motivation to have quality learning outcomes.